2022
DOI: 10.1162/dint_a_00154
|View full text |Cite
|
Sign up to set email alerts
|

COKG-QA: Multi-hop Question Answering over COVID-19 Knowledge Graphs

Abstract: COVID-19 evolves rapidly and an enormous number of people worldwide desire instant access to COVID-19 information such as the overview, clinic knowledge, vaccine, prevention measures, and COVID-19 mutation. Question answering (QA) has become the mainstream interaction way for users to consume the ever-growing information by posing natural language questions. Therefore, it is urgent and necessary to develop a QA system to offer consulting services all the time to relieve the stress of health services. In partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Hajjar and Alagoz developed a randomized modeling framework that provides an accurate solution algorithm and personalized disease screening decision for chronic disease patients or potential chronic disease patients [23]. In addition, multiple scientific studies have shown the significant role of information technology in promoting health and well-being during the COVID-19 pandemic [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Hajjar and Alagoz developed a randomized modeling framework that provides an accurate solution algorithm and personalized disease screening decision for chronic disease patients or potential chronic disease patients [23]. In addition, multiple scientific studies have shown the significant role of information technology in promoting health and well-being during the COVID-19 pandemic [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Named Entity Recognition (NER, (Ratinov and Roth, 2009)) and Relation Extraction (RE, (Bunescu and Mooney, 2005)) are both the key fundamental tasks of Information Extraction and both significant predecessor tasks for building knowledge graphs that are used widely in daily life Ji et al, 2022;Du et al, 2022a). There are two major methods to extract the final result.…”
Section: Introductionmentioning
confidence: 99%